Put your best face forward : the ultimate guide to skincare from Acne to anti-aging - Lee, Sandra, (Dermatologist) (Dey St., an imprint of William Morrow, 2018)
The author presents an entertaining, comprehensive, illustrated skin care guide. Offers essential information on skin care, whether you're hitting adolescence or the middle years--including acne treatments, anti-aging advice, step-by-step tutorials, quizzes, prevention, and tips.